Genetic Association Analysis Reveals Differences in the Contribution of NOD2 Variants to the Clinical Phenotypes of Orofacial Granulomatosis. Issue 7 (July 2016) - Mentzer, Alexander; Nayee, Shalini; Omar, Yasmin; Hullah, Esther; Taylor, Kirstin; Goel, Rishi; Bye, Hannah; Shembesh, Tarik; Elliott, Timothy R.; Campbell, Helen; Patel, Pritash; Nolan, Anita; et al.
Abstract : Background: Orofacial granulomatosis (OFG) is a rare, inflammatory disorder of the mouth, in which some patients also have intestinal Crohn's disease (CD). The etiology remains largely unknown, although there is a high prevalence of atopy, and oral granulomas are also seen in other immune disorders particularly CD and sarcoidosis. We investigated whether genetic variants associated with an increased risk of CD, sarcoidosis, or atopy were also associated with susceptibility to OFG. Methods: Patients were stratified clinically as isolated oral manifestations (OFG only) or concurrent intestinal CD (OFG+CD). We genotyped 201 patients and 1023 healthy controls for risk variants in NOD2, IRGM, IL23R, ATG16L1 (CD), BTNL2 (sarcoidosis), and FLG (atopy). The coding regions of the NOD2 gene were screened for rare, potentially pathogenic variants in OFG. Results: A combined analysis of 3 CD-risk variants in NOD2 showed no association with any OFG subgroup. NOD2 p.L1007insC was associated with OFG+CD ( P = 0.023) and IL23R p.R381Q with all OFG ( P = 0.031). The sarcoidosis risk variant rs2076530 in BTNL2 was associated with all OFG ( P = 0.013). We identified 7 rare missense NOD2 alleles in 8 individuals with OFG, 4 OFG-only patients and 4 patients with OFG+CD. There was a significant enrichment of NOD2 variants in the OFG+CD group compared to the OFG-only group ( P = 0.008, common variants; P = 0.04, all common and rare variants). Conclusions: Our findings suggest that genetic variants in NOD2 are only associated with OFG in patients with concurrent intestinal disease. A genome-wide association scan is needed to fully define the genetic architecture of OFG. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 10 June 2016.